Impact of Wingsail Integration on Seakeeping Performance and Stability of a Fishing Vessel - Hegel Desta Zalayetha; Muhammad Ridwan Utina; Dian Purnamasari; Endah Suwarni; Wiwin Sulistyawati (International Journal of Marine Engineering Innovation and Research, 2026)
Reducing fuel consumption in fishing vessels has become an important issue in improving the efficiency and sustainability of maritime operations, particularly for small and medium-scale fisheries. One potential approach is the integration of wind-assisted propulsion systems such as wingsails. However, the addition of structures above the deck may influence vessel stability and motion responses in waves. This study evaluates the effect of wingsail integration on the seakeeping performance and intact stability of a fishing vessel operating in Benoa, Bali. The reference vessel has principal dimensions of LOA 33.50 m, LPP 29.65 m, breadth 7.95 m, depth 4.06 m, draft 2.90 m, and displacement 415.6 tons. Analysis is conducted using Maxsurf Stability for intact stability assessment and Maxsurf Motion for seakeeping analysis. The seakeeping evaluation considers wave headings of 90°, 135°, and 180° with vessel speeds of 6, 8, and 10 knots, while sea conditions are derived from Beaufort scale conversion. Vessel motions are assessed using RMS, MSI, and MII according to STANAG 4154, while stability is evaluated under departure, fishing ground, and arrival load cases based on IMO Intact Stability Criteria.